2004
DOI: 10.1289/ehp.7216
|View full text |Cite
|
Sign up to set email alerts
|

Drinking-Water Nitrate, Methemoglobinemia, and Global Burden of Disease: A Discussion

Abstract: On behalf of the World Health Organization (WHO), I have undertaken a series of literature-based investigations examining the global burden of disease related to a number of environmental risk factors associated with drinking water. In this article I outline the investigation of drinking-water nitrate concentration and methemoglobinemia. The exposure assessment was based on levels of nitrate in drinking water greater than the WHO guideline value of 50 mg/L. No exposure–response relationship, however, could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
213
0
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(234 citation statements)
references
References 39 publications
3
213
0
18
Order By: Relevance
“…The higher levels of NO 2 -N observed in these three locations may be due to the entry of human sewage into the water. A previous study showed that presence of higher concentrations of NO 2 -N in water is a potential problem due to its toxicity to humans (more potential health effects are seen in infants) and livestock when consumed [49].…”
Section: Physico-chemical and Microbiological Parametersmentioning
confidence: 99%
“…The higher levels of NO 2 -N observed in these three locations may be due to the entry of human sewage into the water. A previous study showed that presence of higher concentrations of NO 2 -N in water is a potential problem due to its toxicity to humans (more potential health effects are seen in infants) and livestock when consumed [49].…”
Section: Physico-chemical and Microbiological Parametersmentioning
confidence: 99%
“…Declining surface water quality directly affects human and ecosystem health, which further impacts economic development and social wellbeing. Degraded water quality may induce various forms of illness, and exhibit reproductive and developmental toxicity (Horrigan et al 2002;Fewtrell 2004;Avalanja and Bonner 2005). Excess nutrient and pollutant loadings have also been linked to several problems in aquatic ecosystems, including increased frequency and severity of harmful algal blooms, dramatic shifts in trophic relationships, direct toxicity to aquatic organisms, and expansion of coastal hypoxic zones (Boesch et al 2001;Ocean Commission 2004;Diaz and Rosenberg 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[11] Although it is not evaluated in our study, MetHb also can develop due to ingestion of nitrates in drinking water or food, dehydration, use of various drugs, and cardiac or respiratory system diseases. [18] Therefore, it is important to consider these factors. Methemoglobinemia is a rare but potentially lethal condition.…”
Section: Discussionmentioning
confidence: 99%